Upaya Pemerintah Malaysia Menanggulangi Masalah Terorisme - Syahrir Mujib; Mhd Halkis (Sospol : Jurnal Sosial Politik, 2022)
This paper aims to explain the counter-terrorism efforts carried out by the Malaysian government. As is well known, Southeast Asia is a region which is the basis for the development of radical groups that lead to acts of terrorism. Malaysia is one of the countries in Southeast Asia that has experienced various acts of terrorism in line with the development of radical groups in the country. There are around 13 (thirteen) radical groups developing in Malaysia. Indeed this is a threat to security and defense. So that the Malaysian government seeks to overcome various acts of terrorism. By using qualitative methods and the concept of deradicalization, this study found that the Malaysian government's counterterrorism efforts were carried out through the implementation of deradicalization programs and cooperation with countries in the Southeast Asian region.